Globalization of science: Evidence from authors in academic journals by country of origin - Vit Machacek (Charles University in Prague, Institute of Economic Studies (IES), 2020)
The scientific community faces an everlasting pressure to publish internationally. This study measures the tendency to publish in globalized journals on a large dataset of journals indexed in the Scopus database. Based on data on 34 964 journals indexed in the Scopus Source List (Scopus 2018), we derived seven globalization indicators. These were subsequently scaled-up to the level of 174 countries and 27 disciplines between 2005 and 2017. The methodology draws from the pioneering work of Zitt and Bassecoulard (1998; 1999). The paper is accompanied by the interactive publication available at http://www.globalizationofscience.com. Advanced countries tend to have high globalization that is not varying across disciplines. Social sciences and health sciences are less globalized than physical and life sciences. The globalization in the former Soviet bloc is lower, especially in social sciences or health sciences. China has profoundly globalized its science system; gradually moving from the lowest globalization rates to the world average. Contrary Russia was constantly among the least globalized during the whole period, with no upward trend.
Keywords: 330; Globalisierung; Wissenschaft; Bibliometrie; Fachzeitschrift; Indexberechnung; Welt